1997
DOI: 10.1038/sj.onc.1201370
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a functional site for Bcl-2 downstream of caspase cascade in preventing apoptosis

Abstract: Apoptotic cell death is driven by ICE family proteases (caspases) and negatively regulated by Bcl-2 family proteins. Although it has been shown that Bcl-2 exerts anti-apoptotic activity by blocking a step(s) leading to the activation of caspases, a role for Bcl-2 and Bcl-x L downstream of the caspase cascade has remained unclear. Here, we show that puri®ed active caspase-3 (CPP32/Yama/apopain) and caspase-1 (ICE) induces apoptosis when microinjected into the cytoplasm of cells, con®rming our recent observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…HeLa cells have been shown to behave as type II cells since overexpression of Bcl-2 prevents CD95-mediated apoptosis (23,36). Treatment of these cells with agonistic anti-Fas/CD95 induced apoptosis in the large majority of cells; however, prior infection with T. gondii significantly blocked Fas/CD95-triggered cell death, as was expected from previous results ( Fig.…”
Section: T Gondii Inhibits Apoptosis In Fas-triggered Type II Cellssupporting
confidence: 75%
“…HeLa cells have been shown to behave as type II cells since overexpression of Bcl-2 prevents CD95-mediated apoptosis (23,36). Treatment of these cells with agonistic anti-Fas/CD95 induced apoptosis in the large majority of cells; however, prior infection with T. gondii significantly blocked Fas/CD95-triggered cell death, as was expected from previous results ( Fig.…”
Section: T Gondii Inhibits Apoptosis In Fas-triggered Type II Cellssupporting
confidence: 75%
“…Cleavage of Bcl-2 might be a means of effectively removing the anti-apoptotic effect of Bcl-2. Current results favour the notion that Bcl-2 functions upstream of caspase activation and prevents apoptosis by suppressing caspase 3 [27][28][29]. Our results have demonstrated that Bcl-2 can act as a downstream substrate of caspase 3 or a caspase-3-like protease, raising the possibility that the cleaved 22 kDa fragment might have a direct role in mediating the amplification of the death effects during apoptosis [22].…”
Section: Discussionsupporting
confidence: 56%
“…Cheng et al [23] have proposed that the cleaved product is capable of acting as a Bax-like death effector. This notion is somewhat controversial in that Bcl-2 is thought to act upstream of caspase-3 activation [29], therefore suggesting that the cleavage of Bcl-2 during apoptosis is a means of preventing its antiapoptotic effects after caspase-3 activation rather than inducing proapoptotic activity. Whether Bcl-2 cleavage to a proapoptotic form during apoptosis does indeed act to amplify the apoptotic response should be an interesting topic for future study.…”
Section: Discussionmentioning
confidence: 99%